Alternative practices to the conventional healthcare model used by caregivers of patients hematologic malignancies - Claudia Patricia Casas Patarroyo; Ana Julia Carrillo; Carmelo Fuentes Restrepo; Lorena Mesa Melgarejo; Ruth Alexandra Castiblanco; Maria Helena Solano (Universidad de Alicante, 2019)
Introduction: Hematological neoplasms have the cultural burden of the word cancer which leads caregivers to look for different alternatives. Objective: To analyse the anthropological link between care and tenderness to potentiate care as an essential "way to be" of the human being, who ontological way was born of care and needs care. Methodology: Descriptive qualitative study. The participants were 17 caregivers, who were selected by convenience. Two discussion groups' sessions were performed. The sessions were recorded and transcribed in full. The analysis followed the Janice M. Morse framework. Results: The findings that emerged permitted an approach toward understanding the practices used to care for patients affected by malignant hematological disease. The practices were organized in three types: 1. Spiritual practices: God´s Will as determinant in the recovery process; 2. Emotional Practices: the familiar ties make more bearable the illness and the treatment, and, 3. Corporal practices: origin products, vegetal, animal, semi-synthetic and no conventional pharmacological products. Conclusion: The utilization of alternative practices is very common by caregivers. Healthcare practitioners cannot ignore this reality and need tools to adequately guide and inform patients and caregivers.